THE PRESENCE OF THE MODERN INFRASTRUCTURE IN THE MIDDLE OF THE TRADITIONAL COMMUNITIES IN EAST TIMOR - GODINHO, CONSTANTINO; KAMEO, DANIEL D; ANTONIUS, BELE (Innovare Journal of Social Sciences, 2020)
Objective: The aim of this study is to find negative impacts of the construction of the modern infrastructure of the toll road and find out a good solution in East Timor. Methods: The research methodology used is descriptive qualitative research methodology, namely, collecting data, interviewing key persons, making data deduction, analyzing data, drawing conclusions, and expressing recommendations, especially for the contractors and for the government. Results: The construction of the toll road infrastructure megaprojects in the new country of Timor-Leste has both positive and negative impacts. The negative impact is huge and this is not taken into account by the contractors and the government in the construction of the Suai-Beasu toll road that connects the city of Suai on the South coast and the town of Dili on the North coast of the Democratic Republic of Timor-Leste. Hence, the recommendations suggested for the contractors and the government are to implement the aspirations of the communities, especially in the fair and just payment for the area used for the projects and building new cross-traffic for the residents alongside the toll road. Conclusion: The presence of the toll road had positive impacts but there are several negative impacts on the lives of the Suai people, therefore, it is better that if the government and the contractors pay serious attention to overcome the negative impacts.